2006
DOI: 10.1007/s10548-006-0006-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivities of the Freshly Excised Cerebral Cortex in Epilepsy Surgery Patients; Correlation with Pathology, Seizure Duration, and Diffusion Tensor Imaging

Abstract: The electrical conductivities (sigma) of freshly excised neocortex and subcortical white matter were studied in the frequency range of physiological relevance for EEG (5-1005 Hz) in 21 patients (ages 0.67 to 55 years) undergoing epilepsy neurosurgery. Surgical patients were classified as having cortical dysplasia (CD) or non-CD pathologies. Diffusion tensor imaging (DTI) for apparent diffusion coefficient (ADC) and fractional anisotropy (FA) was obtained in 9 patients. Results found that electrical conductivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 37 publications
5
35
0
Order By: Relevance
“…In their report, the conductivity values of gray matter and white matter were estimated to be 0.1 and 0.06 S/m, respectively, at the low-frequency limit (below 100 Hz). Akhtari et al [2006] measured conductivities and ADC values of excised cerebral cortex in epilepsy surgery patients, and found a negative correlation between these two quantities. This result seems to disagree with our model and other relevant articles [Verheul et al, 1994;Wang et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…In their report, the conductivity values of gray matter and white matter were estimated to be 0.1 and 0.06 S/m, respectively, at the low-frequency limit (below 100 Hz). Akhtari et al [2006] measured conductivities and ADC values of excised cerebral cortex in epilepsy surgery patients, and found a negative correlation between these two quantities. This result seems to disagree with our model and other relevant articles [Verheul et al, 1994;Wang et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…Such findings support the concept that CSF flow within the brain is probably altered related to the severe cortical and white matter disorganization in hemimegalencephaly cases rather than changes in brain compliance or due to blood and tissue debris since CD cases had lower rates of needing shunts despite similar ages at surgery, ventricular size, and expected blood loss during surgery. 1,2,11 Alternately, differences in etiology may contribute to the ability of the arachnoid granulations to remain open after resection-disconnection hemispherectomy. While acute changes in CSF osmolarity reflected by increased CSF RBC counts may also contribute to developing hydrocephalus, our data suggest that this is a minor association.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Tuch et al (2001), using an effective medium approach, demonstrated a strong linear relationship between the conductivity and the diffusion tensor eigenvalues. A phantom validation study performed by Oh et al (2006) with silk yarn confirmed this relationship; however, an in vitro experiment on freshly excised neocortex and subcortical white matter of epilepsy patients undergoing neurosurgery found large variations in electrical conductivities and was unable to verify linear relationships (Akhtari et al, 2006).…”
Section: Introductionmentioning
confidence: 97%